Strategi Pembelajaran Membaca Al-Qur’an melalui Metode Yanbu’a Bagi Santri Kalong di Pondok Pesantren Ar-Ridha Kendal - Maula, Nely Nimatal; Muthohar, Sofa; Asiyah, Nur (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2025)
Many Islamic boarding school students still experience difficulties in reading the Qur'an with tartil. This condition presents both a challenge and an opportunity for Islamic boarding schools to implement effective learning strategies. This study describes the enactment and output of learning to read the Qur'an using the Yanbu'a method for bat students. This study used a descriptive qualitative method. Data were collected through observation, interviews, and documentation at the Ar-Ridha Kendal Islamic Boarding School. The results of this study indicate that learning to read the Qur'an using the Yanbu'a method is implemented adaptively. The methods used include intensive and gradual learning, talaqqi and mushafahah-based learning, and providing targets and periodic evaluations. The learning output shows positive developments in bat students' reading the Qur'an, namely the ability to read according to tajwid rules and complete Yanbu'a learning.